Perubahan Bunyi Bahasa Indonesia dalam Pemerolehan Bahasa pada Anak Usia 3-4 Tahun di Desa Jagaraga, Kecamatan Kuripan, Kabupaten Lombok Barat: Kajian Psikolinguistik - ., Harani; Suparwa, I Nyoman; Teguh, I Wayan (Stilistika : Journal of Indonesian Language and Literature, 2022)
This study entitled "Changes in Indonesian Language Sounds in Language Acquisition in Children Age 3-4 Years, in Jagaraga Village, Kuripan District, West Lombok Regency: A Psycholinguistic Study" which discusses changes in sounds that occur in the speech of children aged 3-4 years and the cause of the change in sound. In this study, researchers focused more on children who use Indonesian as their first language or mother tongue. Children's language development starts from the family and largely depends on the attention of parents and those around them. Language acquisition is associated with mastering a language without being based directly, that is, without going through formal education to teach it. This study uses a descriptive qualitative method, because the data studied are in the form of words not numbers, namely the observation/interview method with qualitative analysis techniques and the presentation of the results of data analysis is carried out using formal and informal methods (Sudaryanto, 2014: 214).The results of this study indicate that the types of sound changes found in the speech of children aged 3-4 years are assimilation, vocal modification, neutralization and zeronization and anaptiksis. Sounds that experience changes in the speech of children aged 3-4 years are dominated by sound [r] and sound [s]. This is because the growth of the articulatory organ in children is not perfect, causing children to have difficulty pronouncing sounds. This case is often referred to as lisp, which is a condition where a person has difficulty pronouncing certain letters or words correctly (Halodoc, 2018). There are internal factors and external factors that influence the cause of sound changes in children aged 3-4 years.